Employees’ Turnover Intention in Nepalese Commercial Banks - Adhikari, Pitri Raj (The International Research Journal of Management Science, 2021)
This paper attempts to investigate the factors influencing the employees’ turnover intention in Nepalese commercial banks. It has employed descriptive and causal comparative research design to estimate the relationship between dependent (employees’ turnover) and independent variables (compensation, organizational justice, organizational culture, leadership empowerment behavior, job stress). To achieve the purpose of the study structured questionnaire was prepared and distributed to 540 respondents of 27 commercial banks but only 300 usable questionnaires are received. Mean, standard deviation, correlation and multiple regression model are used to analyze the data. Employees’ turnover intention is positively and significantly correlated with all independent variables. It is found that organizational justice is the most influencing factor followed by organizational culture whereas compensation is the least influencing factor for employees’ turnover intention in Nepalese commercial banks. This study is an endeavor to extend the literature of employees’ turnover intention in banking industry.